In situ formation of square shaped Fe2B borides in coated surface produced by GTAW - Yaz, Mehmet (Natl Inst Optoelectronics, 2013)
In this investigation, a gas tungsten arc welding (GTAW) is used as a high energy density beam to form a surface over 0.15% C carbon steel with FeB and Graphite powders. The microstructure, microhardness and dry-sliding wear behavior of the composite coating were investigated using optical micrograph (OM), X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDS), microhardness tester and adhesive wear tester. A lot of types of carbide and borides were formed. Fe2B, B4C, Fe3C, FeB, Fe3B, Fe7C5, C and alpha-Fe phases were seen in coated surfaces. The shape of the graphite present in the FeB-C composite TIG welding coatings is various from sheet-like to spherical. Within the wear test conditions used in the present research, on Fe2B coated samples wear was essentially oxidative until the failure of the coating.
Keywords: Fe2B; Adhesive wear; GTAW; SEM; Coating